Cytoplasmic receptor for glucocorticoids in lung of the human fetus and neonate. - Ballard, P L (1974)
In fetal animals, glucocorticoids accelerate development of the lung and cause precocious appearance of alveolar surfactant. To determine if the human lung also can respond to corticosteroids, we examined lungs of the human fetus and neonate for both cytoplasmic binding and nuclear uptake of glucocorticoids. In slices of fetal lung incubated with [3H]dexamethasone at 2 degrees C, specific macromolecular binding occurs primarily in the "cytoplasmic" fraction. After further incubation at 37 degrees C. nearly 75% of the radioactivity localizes in the "nuclear" fraction with a concentration of 0.3 pmol/mg DNA at apparent dexamethasone saturation (47 nM). The cytoplasmic receptor binds dexamethasone in vitro with high affinity (dissociation constant = 8.9 nM), and the affinity of various other steroids correlates with their glucocorticoid potency. Receptor was present in lungs of fetuses and neonates of gestational age 12-43 wk, with a mean concentration in hysterotomy specimens of 0.24 pmol sites/mg cytosol protein. Similar binding activity was present at lower concentration in fetal liver, gut, kidney, heart, muscle, and skin. Cytoplasmic receptor was not detected in lung and liver of premature infants with respiratory distress syndrome. This deficit appears to result from increased levels of endogenous steroids (mean cortisol 45.5 micrograms/100 ml cytosol) as well as inactivation of receptor secondary to the illness. Thus, the lung of the human fetus and neonate contains the receptor mechanism necessary for direct responsiveness to glucocorticoids. These findings support the potential usefulness of these hormones in prevention of respiratory distress syndrome in the premature infant.